A study on semi-active Tuned Liquid Column Dampers (sTLCDs) for structural response reduction under random excitations. (3rd February 2016) - Sonmez, E.; Nagarajaiah, S.; Sun, C.; Basu, B.
Abstract: This paper proposes a new model for semi-active Tuned Liquid Column Damper (sTLCD) where the sTLCD is connected to the primary structure using an adaptive spring. Short time Fourier transformation (STFT) based control algorithms (feedforward and feedback) are developed to control the stiffness of the spring such that the sTLCD is tuned in real-time when the dominant excitation frequency varies or damage occurs to the primary structure. The effectiveness of the proposed sTLCD and the associated control algorithms is examined numerically under random excitations including stationary and non-stationary excitations. Root Mean Square (RMS) response is computed in three cases: with no TLCD, with a passive Tuned Liquid Column Damper (pTLCD) and with the sTLCD. Results indicate that the developed control algorithms are effective in tuning the frequency of the sTLCD in real-time. As a result, the sTLCD provides more robust reduction than the pTLCD because the pTLCD becomes off-tuned and loses its effectiveness when the properties of the excitations or the primary structure vary.